2015
DOI: 10.1155/2015/439382
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Binary CO2/CH4 Mixture Breakthrough Profiles in MIL‐53 (Al)

Abstract: MIL-53 (Al) aluminum terephthalate, a commercial metal-organic framework, has been studied as a potential candidate for pressure swing adsorption separation of CO2/CH4binary mixtures. Pure gas isotherms of CH4and CO2measured over 0–6 MPa and at room temperature are fitted with the Dubinin-Astakhov (D-A) model. The D-A model parameters are used in the Doong-Yang Multicomponent adsorption model to predict the binary mixture isotherms. A one-dimensional multicomponent adsorption breakthrough model is then used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The highest breakthrough time is recorded for run1 at 5 bar while the lowest one is observed in run 3 at 25 bar. The same behavior was mentioned by Gomez et al while applying experiments for adsorption CO2 from CO2/CH4 mixture stream by aluminum terephthalate MOF-MIL-53 (Al) 14).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The highest breakthrough time is recorded for run1 at 5 bar while the lowest one is observed in run 3 at 25 bar. The same behavior was mentioned by Gomez et al while applying experiments for adsorption CO2 from CO2/CH4 mixture stream by aluminum terephthalate MOF-MIL-53 (Al) 14).…”
supporting
confidence: 72%
“…Gomez et al developed a one-dimensional (1D) adsorption breakthrough model using COMSOL Multiphysics for binary mixture CO2/CH4 to validate the experimental data for capturing CO2 by Metal Organic Framework (MOF) material, MOF-MIL-53(Al). 14) They took into account the effect of total and bed porosities. They validated the proposed model by simulating the breakthrough of CO2/H2 mixture in a column of activated carbon and compared the results with the experimental data from literature by Casas et al 15) The results showed a good agreement between developed model and experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devic et al [28] and Gomez et al [40] have also reported measurement of 1 : 1 methane/carbon dioxide adsorption in MIL(53)Cr and MIL(53)Al, respectively, which will concern us here. Other relevant simulations are those of Snurr and co-workers [41].…”
Section: Introductionmentioning
confidence: 82%
“…Using the parameters for the pure single components, binary mixture isotherms of methanedioxide were calculated using both approaches, sharp transition, model A and gradual transition, model B at various carbon dioxide mole fractions (0, 0.2, 0.5, 0.8 and 1) are presented in figures 3 and 4 for 294 and 304 K, respectively. To reproduce the essential features of the mixture isotherms of Baron and co-workers [37] and also the equimolar mixture isotherm of Gomez et al [40], we have adjusted the interaction parameter J ab to 198k indicating that CH 4 and CO 2 molecules in a pore experience an effective repulsion possibly due to competition for the same binding sites. 4.…”
Section: Adsorption Isotherms Of Methane/carbon Dioxide Mixturesmentioning
confidence: 99%